2005
DOI: 10.1139/y05-015
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1 adrenergic receptor control of renal blood vessels during aging

Abstract: Aging humans and rats have a reduced renal vascular constriction response to stress, change in posture, or exercise. In this study, renal interlobar arteries from 9- (intermediate age) to 15-month-old (aging) male Wistar rats constricted less to alpha-adrenergic agonists than those of 4-month-old (young adult) rats. The reduced contraction to A61603 (alpha 1 A agonist) was similar to that to norepinephrine and phenylephrine. Therefore, it appears that the reduction in constriction is primarily related to alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…General transcription inhibitor actinomycin D, but not translational inhibitor cycloheximide, abolished the DSPinduced depressed contraction to norepinephrine, indicating that a transcriptional mechanism is responsible for this downregulation. It has been demonstrated that, in rat mesenteric artery, norepinephrine induces vasoconstriction mainly via α 1A -adrenoceptor receptor [10,15]. This is well in line with our findings that the DSP-induced depressed contractile response to norepinephrine links with the decrease in α 1Aadrenoceptor mRNA expression in the smooth muscle, but not α 2 -adrenoceptor.…”
Section: Discussionsupporting
confidence: 92%
“…General transcription inhibitor actinomycin D, but not translational inhibitor cycloheximide, abolished the DSPinduced depressed contraction to norepinephrine, indicating that a transcriptional mechanism is responsible for this downregulation. It has been demonstrated that, in rat mesenteric artery, norepinephrine induces vasoconstriction mainly via α 1A -adrenoceptor receptor [10,15]. This is well in line with our findings that the DSP-induced depressed contractile response to norepinephrine links with the decrease in α 1Aadrenoceptor mRNA expression in the smooth muscle, but not α 2 -adrenoceptor.…”
Section: Discussionsupporting
confidence: 92%
“…Previous publications from our laboratories Passmore et al, 2005] reveal that both Wistar and Munich Wistar rat interlobar arteries show similar age-and gender-related changes in interlobar artery contraction. Figure 1 provides an overall synopsis of species, gender, and age concepts for interlobar artery contraction.…”
Section: Adrenergic Control Of the Renal Circulationmentioning
confidence: 61%
“…The alpha-1 A receptor is the predominant alpha-1 adrenergic receptor subtype, which mediates vasoconstrictor responses to exogenously administered norepinephrine in the perfused kidney of the adult rat [Blue et al, 1995;Passmore et al, 2005].…”
Section: Adrenergic Control Of the Renal Circulationmentioning
confidence: 99%
“…In human males, a marked decline in baroreflex buffering of blood pressure is due to, at least in part, a marked reduction in a-adrenergic receptor function (Castellani et al 1999;Jones et al 2003). Speculation on how these findings could be reconciled might include: 1) a comparison of prazosin binding in the rat parotid cell indicating a naturally occurring post-a-adrenergic receptor defect in signal transduction (Ishikawa et al 1989); 2) Age-related impairments in a-adrenergic responsiveness could be partially caused by alterations in the coupling of a-adrenergic receptors and G-proteins (Myamoto et al 1992); 3) A decline in the G protein amplification of constriction (Robert et al 1998) and 4) Competitive binding experiments (prazosin) revealed that maximal binding of the a-adrenergic receptor of the interlobar arteries is reduced 25% by 10 months of age and 50% by 18 months of age (Passmore et al 2005). We speculate that the a-adrenergic receptor density or downstream signaling (specifically the G-protein cascade) events are altered as a function of age in the male rat; pointing to the possibility that the a-adrenergic receptors are down-regulated (Parekh et al 2004).…”
Section: Discussionmentioning
confidence: 99%